The identification of translesion DNA synthesis regulators: inhibitors in the spotlight - Bertolin, Agustina Paola (2015)
Over the past half-century, we have become increasingly aware of the ubiquity ofDNA damage. Under the constant exposure to exogenous and endogenous genomic stress, cells must attempt to replicate damaged DNA. The encounter of replication forks with DNA lesions triggers several cellular responses, including the activation of translesion DNA synthesis (TLS), which largely depends upon specialized DNA polymerases with flexible active sites capable of accommodating bulky DNA lesions. A detrimental aspect of TLS is its intrinsic mutagenic nature, and thus the activity of the TLS polymerases must ideally be restricted to synthesis on damaged DNA templates. Despite their potential clinical importance in chemotherapy, TLS inhibitors have been difficult to identify since a direct assay designed to quantify genomic TLS events is still unavailable. Herein we discuss the methods that have been used to validate TLS inhibitors such as USP1, p21 and Spartan, highlighting research that has revealed their contribution to the control of DNA synthesis on damaged and undamaged templates.